The Influence of Note Taking Habits on Students’ Behavior in Madiun City - Nartini Nartini; Reni Setyowati Agustina; Muhammad Hanif (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
Note-taking is the process of recording information by writing down ideas, explanations, or important points for future reference. For students, note-taking serves as an essential learning strategy that facilitates knowledge retention, comprehension, and the development of academic potential. This study aims to examine the impact of students' note-taking habits during teachers' classroom explanations on student behavior in Madiun City, Indonesia. A qualitative descriptive approach was employed, with data collected through interviews with 45 students, classroom observations, and documentation. The data were analyzed using qualitative techniques. Guided by behavioral theory, which emphasizes that environmental stimuli influence individual responses, this study explored how note-taking habits shape students' attitudes and behaviors. The findings indicate that students who consistently take notes demonstrate more positive behaviors, greater preparedness for future challenges, and stronger learning motivation than those with limited note-taking habits. Although digital technology and internet access have transformed learning practices, the study highlights that handwriting remains an important means of fostering critical thinking, preserving personal identity, and maintaining national values. Digital technology should be viewed as a tool for educational advancement, whereas writing continues to serve as a foundation for meaningful learning and character development.